# algebra2

Solve each of the following quadratic equations.
can some explain how to do these kinds of problems

4x^2=13x+12

i believe if i am understanding this i am supose to add to where i get =0
4x^2-13x+12=0
now what do i need to do
I am thinking factoring but I am not sure how to do this part

4x^2 - 13x - 12 = 0

It does factor, I will give you a hint:
one of the factors is x-4

You must have been taught at least one general method to factor those quadratics that do factor.

It has been a while since i worked with any algebra
but i think i can remember some so this is what i got see if i am correct please
4x^2-13x-12=0
(4x+3)(x-4)=0
4x+3=0 0r x-4=0
4x=-3
4x/4=-3/4
x=-3/4

x-4=0
x=4

(-3/4,4)

did i do this right

yes, good for you.

it seems to be correct

## Similar Questions

1. ### math

can someone show me the steps for this problem because i got it incorrect in my exam. Solve each of the following quadratic equations. 4x^2=13x+12 what i had put was that x is 3/4 and x is -4 but i just got my result back and it
2. ### Algebra

Can you pleas Solve the quadric equation step by step 4x square =13x+2 4x^2 = 13x + 2 subtract 13x and 2 from both sides 4x^2 - 13x - 2 = 0 Now use the quadratic formula, since it does not factor.
3. ### math

Still looking at how to solve these... Both are cubic polynomials? 43x^3 + 13x^2 + 18x - 456 = 0 DO I divide first by x-1? 2x(3x+2)^2=312 Honestly: I would graph the equations and find the roots first. I don't see them off hand.
4. ### Algebra

Hello all - I would like to check my work on 2 problems. Solve by factoring : x^2-13x= -12 x^2-13x+12= -12 + 12 x^2-13x+12= 0 (x-1)(x-12)= 0 x = 1 , 12 Solve using the square root property: 2x^2-35=15 2x^2-35-15=0 2x^2-50=0
5. ### math practice help

add or subtract (2x^2+6x+1)+(-7x^2+2x-3) 5x^2-4x-2 -5x^2+8x-2 5x^2-8x+2 -9x^2-8x+2 (3x^2-7x-4)-(6x^2-6x+1) -3x^2-x-5 -3x^2-13x+5 9x^2-x+5 3x^2-13x-5 These are just practice problems. could someone help me figure out how to solve
6. ### Algebra2

Find the polynomials roots to each of the following problems: #1) x^2+3x+1 #2) x^2+4x+3=0 #3) -2x^2+4x-5 #3 is not an equation. Dod you omit "= 0" at the end? #2 can be factored into (x+1)(x+3) = 0, so the roots are x=-1 and -3.